Palms as rainforest resources: how evenly are they distributed in Peruvian Amazonia? - Vormisto, J.
The distribution and the abundance of a species define the limits of its potential use. Despite this simple fact, there are only a few studies that have quantified the actual abundance and the distribution of species/resources in Amazonian rainforests, especially within unflooded (tierra firme)forests. The present study focused on the distributions and the abundances of palms, since they are both structurally important and widely utilized in the forests of Amazonia. The similarity of the palm communities at eight different sites in tierra firme forests of Peruvian Amazonia were examined, and the eight economically most important palm species were selected for more detailed studies on abundance and population structure. The results showed that both the overall palm community composition and the abundances of the eight focal palm species varied among the sites, and that these differences in abundances were related to the amount of exchangeable cations in the soils. Population structure differed between growth forms: large, solitary palm species were mainly represented by seedlings and juveniles, whereas small, clonal palm species had very few seedlings. The great variability in abundance of palm species should be taken into account when estimating the availability of palm resources, as well as in conservation planning of the palm species in an area of interest.
Keywords: ABUNDANCES; ARECACEAE; DISTRIBUTION PATTERNS; NON-TIMBER FOREST PRODUCTS; PERU; UTILIZATION POTENTIAL